2004
DOI: 10.1111/j.1444-0938.2004.tb05064.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of petroleum derivatives and solvents on colour perception

Abstract: Background Occupational exposure to various neurotoxic chemicals has been shown to be associated with colour vision impairment. It seems that this can occur at low exposure levels, sometimes well below the recommended occupational threshold limits. This study was undertaken to determine the effect of exposure to petroleum derivatives (polyethylene, polystyrene) and solvents (perchloroethylene) on colour perception. Methods: Colour vision was assessed using the Ishihara plates, the D-15 test and the Farnsworth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…With respect to color vision, the decrements we observed among adults exposed prenatally and in early life agree with observations among adults exposed occupationally (Gobba et al 1998; Sharanjeet et al 2004). We found a larger difference in CCI among the high PCE–exposure group than the low-exposure group when each was compared with the unexposed group.…”
Section: Discussionsupporting
confidence: 89%
“…With respect to color vision, the decrements we observed among adults exposed prenatally and in early life agree with observations among adults exposed occupationally (Gobba et al 1998; Sharanjeet et al 2004). We found a larger difference in CCI among the high PCE–exposure group than the low-exposure group when each was compared with the unexposed group.…”
Section: Discussionsupporting
confidence: 89%
“…reported that there was both blue yellow and nonpolar defects found in workers exposed to organic solvents when compared to controls. [18] The change in color vision could be attributed to more number of exposure years in the same environment.…”
Section: Discussionmentioning
confidence: 99%